"It's just inappropriate": Harassment of dental students by patients. Issue 5 (23rd December 2021) - Liaw, Royston D.Y.; Ling, Dobson C.T.; Vuli, Lia J.; Loch, Carolina; Adam, Lee A.
Abstract: Introduction: Harassment is an issue that occurs in all workplaces and institutions. Due to increased exposure to patients, higher rates of harassment are experienced in health care systems. Health care workers need to form a professional relationship with patients to attend to their health care needs; however, harassment by patients can disrupt this relationship and have detrimental physical, mental, and emotional impacts on the health practitioner. Objective: The purpose of this study was to examine the prevalence and impact of harassment by patients toward clinical students at a prominent Australasian dental school. Methods: A 14‐item survey was distributed to clinical students. The survey collected basic demographic information and contained Likert‐scale closed questions on harassment prevalence and experience and a free text question asking for details of a significant harassment experience. Descriptive statistics and analysis of free text data were performed. Results: The response rate was 67%. About 20% of respondents reported experiencing at least one incident of harassment. Verbal harassment was most commonly reported, followed by sexual and racial harassment. All incidences of sexual harassment were reported by female students, while racial harassment was most frequently reported by students of Asian ethnicity. Most students indicated they were unsure of how to respond to harassment by patients. Conclusion: Dental students were exposed to harassment by patients. Implications: Appropriate policies and education on responding to harassment, alongside support for the same, could help ensure the safety and wellbeing of students.